PENDEKATAN SEMIOTIK MEME SINEMA KEKINIAN - Setiawan, I Nyoman Anom Fajaraditya (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Cinema has now penetrated various lines of viewers' lives. Apart from being entertainment, cinema also has an impact on the development of visualization in the social sphere. In the development of such a massive cinema, the insertion of various messages in the story plot gave rise to various perceptions. The results of the cinema work were then broken into a creative criticism that had a social message. One of the pieces is in the form of meme visualization. Meme then returns to producing signs that are many times over. In this meme discourse, it uses semiotic adherence based on several popular cinemas today. Data collected is based on searches from internet media that have related keywords. Then the data is analyzed by digging in terms of denotations and connotations in the semiotic domain. So the meme analysis then provides a new perspective on the catch of meaning in the contemporary cinema. The new perspective will also provide a new analysis of social assessment from the viewpoint of popular cinema viewers. Keywords: semiotics, memes, cinema, present